Analisis Kesulitan Siswa SMA dengan Gaya Belajar Visual dalam Menyelesaikan Soal HOTS - Prasetyo Budi Darmono; Mei Wijayadi; Nila Kurniasih (SAP (Susunan Artikel Pendidikan), 2021)
The difficulties of student in solving HOTS problems are caused by some factors. One of them is student learning style. Student learning styles are divided into three types, namely visual, auditorial, and kinesthetics. This research focuses on visual learning style. This research uses a qualitative method aiming to describe the difficulties of student in solving HOTS mathematic problems by visual learning style. The subject was taken using snowball sampling and purposive sampling technique. The data collection techniques were questionnaire, test, interview, and note range. Analysis techniques used on in this research were data reduction, data display and conclusion drawing. The result of this research was student who had a visual learning style got difficulty in using concept at problem with C6 grade. That was because the students were not familiar with HOTS problems.